Isolation and characterisation of neural progenitor cells from the adult Chx10(orJ/orJ) central neural retina. - Kokkinopoulos, I; Pearson, R; Macneil, A; Dhomen, N; Maclaren, R; Ali, R; Sowden, J (2008)
Retinal stem cells have been isolated from the ciliary epithelium (CE) of the mammalian retina. However, the central neural retina (CNR) lacks the capability to regenerate, a phenomenon retained by lower vertebrates. Mutations in the Chx10 homeobox gene cause reduced proliferation of retinal progenitor cells during development, leading to microphthalmia. Recently, we showed that in Chx10(orJ/orJ) mice, dividing cells persist in the adult CNR, suggesting the existence of a dormant progenitor population. Here, we show that these cells are proliferative and give rise to neurospheres in vitro, a characteristic of neural stem cells. However, these adult-derived CNR progenitors differ from those of the wildtype CE, leading to de-pigmented, larger and more numerous neurospheres expressing Müller glial cell markers. Our results suggest that lack of Chx10 leads to maintenance of a dormant neural progenitor population in the adult CNR. Furthermore, Chx10 is not required for in vitro proliferation of these progenitors.